Techno-economic studies of low GWP-organic Rankine cycle for low-level geothermal waste heat utilization in Remote Island of Indonesia - Fefria Tanbar; Rusdi Febriyanto; Hifni Mukhtar Ariyadi; Ariyana Dwiputra Nugraha; Arionmaro Asi Simaremare; Eko Supriyanto; Meiri Triani; Muhammad Akhsin Muflikhun (Case Studies in Thermal Engineering)
With global decarbonization trends, the energy supply challenge persists, especially in archipelagic nations like Indonesia. The Ulumbu Geothermal Power Plant at Flores Island of Indonesia currently uses a type of back pressure where the expanded steam is discharged directly to the atmosphere at a pressure of 0.98 bar and a temperature of 98.7 °C. This steam could be harnessed to generate electrical energy using Organic Rankine Cycle system. This study thermodynamically and economically assessed two ORC systems: Binary Cycle-Organic Rankine Cycle (BC-ORC) and Recuperator (BC-ORCR), both using low global warming potential (GWP) working fluids of R1233zd (E), R1224yd (Z), R1234ze (Z), R1234ze (E), R1243zf, and R1234yf, paired with air- and water-cooled condensers. The results indicate that the BC-ORCR system with a water-cooled condenser using R1233zd (E) as the working fluid achieved the highest net output power value and system efficiency of 2213 kW and 10.14 %, respectively. This could support up to 65 % of the electricity load of the GI Ulumbu and GI Ruteng substations. Economically, this system also emerged as the most favorable option, offering the highest production capacity, with a TL Sales Target of 16,476,847 USD, a net present value (NPV) of 3,982,761 USD and a Payback Period of 9.39 years, outperforming other systems in the analysis.